2012
DOI: 10.1002/humu.22063
|View full text |Cite
|
Sign up to set email alerts
|

Differential MicroRNA expression tracks neoplastic progression in inflammatory bowel disease-associated colorectal cancer

Abstract: One of the most serious complications faced by inflammatory bowel disease (IBD) is the potential development of colorectal cancer (CRC). There is a compelling need to enhance the accuracy of cancer screening of IBD patients. MicroRNAs (miRNAs) are small non-protein-coding RNAs that play important roles in CRC oncogenesis. In this study, we report differential miRNA expression in IBD patients with associated CRC, from non-neoplastic tissue to dysplasia and eventually cancer. In addition, we identify and examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 13 publications
1
34
1
1
Order By: Relevance
“…However, colon epithelial cells express very low levels of suppressive miR-122 [41], resulting in higher CAT-1 expression. In CRC cells miR-122 was even down-regulated, indicating a loss of control of CAT-1 expression [42]. Third, although CAT-1 protein on the cellular membrane mediates both influx/efflux and exchange of its substrates, arginine, lysine, and ornithine, between intracellular and extracellular pools, differential expression of CAT-1 protein on the plasma membrane of different organelles within the cells may regulate these amino acid pools in different organelles [32].…”
Section: Discussionmentioning
confidence: 99%
“…However, colon epithelial cells express very low levels of suppressive miR-122 [41], resulting in higher CAT-1 expression. In CRC cells miR-122 was even down-regulated, indicating a loss of control of CAT-1 expression [42]. Third, although CAT-1 protein on the cellular membrane mediates both influx/efflux and exchange of its substrates, arginine, lysine, and ornithine, between intracellular and extracellular pools, differential expression of CAT-1 protein on the plasma membrane of different organelles within the cells may regulate these amino acid pools in different organelles [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the last 4 years, several studies have demonstrated the potential of miRNAs in PTC diagnosis. Although miR-146b-5p is down-regulated in other types of cancer (11)(12)(13), this miRNA is highly overexpressed in PTCs (14,15), reliably distinguishing this type of cancer from follicular carcinoma (FTC), and from benign lesions (16,17). Moreover, Schwertheim and cols.…”
Section: Amentioning
confidence: 99%
“…It was found that miR-214 targets FGFR1 in CRC cells and it was proposed that downregulation of miR-214 is associated with CRC liver metastasis [68]. Another study reported that miR-214 along with other miRNAs was one which altered the p53 pathway and caused CRC [69]. Recent literature has also suggested that downregulation of miR-214 in CRC tissue leads to lung metastasis [70].…”
Section: • Mir-214 In Colorectal Cancermentioning
confidence: 94%